Physiological potential of stored Schinopsis brasiliensis Engler diaspores - Alves Diniz da Silva, Monalisa (Revista Ciência Agronômica, 2021)
Storage of diaspores makes it possible to provide seedlings for reforestation programs or restoration of degraded areas, especially for perennial species that do not regularly produce diaspores or when germination is diffi cult and slow. The objective of the present study was to verify the physiological potential of Schinopsis brasiliensis diaspores stored in two environments for 12 months, with subsequent manual scarifi cation of the endocarp. The experimental design was entirely randomized, using a 2 × 7 × 2 factorial scheme, with two environments (natural and refrigerator), seven periods (0, 2, 4, 6, 8, 10 and 12 months) of storage, and two physical conditions of the endocarp (intact and scarifi ed). The study analyzed water content, emergence, speed index and mean emergence time, length and dry mass of the aerial part and root system, and collar diameter of the seedlings. The 12 month storage did not overcome the tegument dormancy of S. brasiliensis diaspores. After storage in the natural environment, manual scarifi cation favored emergence and the seedlings’ speed of establishment. The diaspores presented increased germination capacity at fi ve months and decreased seedling development before losing their germination capacity, regardless of storage conditions.